Growth hormone treatment in Prader-Willi syndrome patients: systematic review and meta-analysis - Caroline de Gouveia Buff Passone; Ruth Rocha Franco; Simone Sakura Ito; Evelinda Trindade; Michel Polak; Durval Damiani; Wanderley Marques Bernardo (BMJ Paediatrics Open)
Background Growth hormone (GH) treatment is currently recommended in Prader-Willi syndrome (PWS) patients.Objectives To evaluate the impact (efficacy and safety) of the use of recombinant human GH (rhGH) as a treatment for PWS.Method We performed a systematic review and, where possible, meta-analysis for the following outcomes: growth, body mass index, body composition, cognitive function, quality of life, head circumference, motor development/strength, behaviour and adverse effects. We included all PWS patients, with all types of genetic defects and with or without GH deficiency, who participated in rhGH studies performed in infancy, childhood and adolescence, that were either randomised controlled trials (RCTs) (double-blinded or not) or non-randomised controlled trials (NRCTs) (cohort and before and after studies). The databases used were MEDLINE, Embase and Cochrane Central.Results In 16 RCTs and 20 NRCTs selected, the treated group had an improvement in height (1.67 SD scores (SDS); 1.54 to 1.81); body mass index z-scores (−0.67 SDS; −0.87 to −0.47) and fat mass proportion (−6.5% SDS; −8.46 to −4.54) compared with the control group. Data about cognition could not be aggregated.ConclusionBased on high quality evidence, rhGH treatment favoured an improvement of stature, body composition and body mass index, modifying the disease’s natural history; rhGH treatment may also be implicated in improved cognition and motor development in PWS patients at a young age.Ethics and dissemination The current review was approved by the ethical committee of our institution. The results will be disseminated through conference presentations and publications in peer-reviewed journals.PROSPERO registration number CRD42019140295